In vivo measurement of vocal fold surface resistance. (2nd June 2017) - Mizuta, Masanobu; Kurita, Takashi; Dillon, Neal P.; Kimball, Emily E.; Garrett, C. Gaelyn; Sivasankar, M. Preeti; Webster, Robert J.; Rousseau, Bernard
Abstract : Objectives/Hypothesis: A custom‐designed probe was developed to measure vocal fold surface resistance in vivo. The purpose of this study was to demonstrate proof of concept of using vocal fold surface resistance as a proxy of functional tissue integrity after acute phonotrauma using an animal model. Study Design: Prospective animal study. Methods: New Zealand White breeder rabbits received 120 minutes of airflow without vocal fold approximation (control) or 120 minutes of raised intensity phonation (experimental). The probe was inserted via laryngoscope and placed on the left vocal fold under endoscopic visualization. Vocal fold surface resistance of the middle one‐third of the vocal fold was measured after 0 (baseline), 60, and 120 minutes of phonation. After the phonation procedure, the larynx was harvested and prepared for transmission electron microscopy. Results: In the control group, vocal fold surface resistance values remained stable across time points. In the experimental group, surface resistance (X% ± Y% relative to baseline) was significantly decreased after 120 minutes of raised intensity phonation. This was associated with structural changes using transmission electron microscopy, which revealed damage to the vocal fold epithelium after phonotrauma, including disruption of the epithelium and basement membrane, dilated paracellular spaces, and alterations to epithelial microprojections. In contrast, control vocal fold specimens showed well‐preserved stratified squamous epithelia. Conclusions: These data demonstrate the feasibility of measuring vocal fold surface resistance in vivo as a means of evaluating functional vocal fold epithelial barrier integrity. Device prototypes are in development for additional testing, validation, and for clinical applications in laryngology. Level of Evidence: NA Laryngoscope, 127:E364–E370, 2017